Environmental DNA metabarcoding shows potential for monitoring meiofauna and marine nematodes diversity in mangrove ecosystems in China - Mingcheng Hu; Yuqing Guo; Fenfen Ji; Yijia Shih; Kai Liu; Xiangxiang Yi; Yuanxin Fan (Ecological Indicators)
Mangrove ecosystems, located at the vital interface between land and sea, exhibit exceptionally high biodiversity. Meiofauna are key components in the food webs and nutrient cycles of mangrove ecosystems. However, the diversity of intertidal meiofauna is not well understood, primarily due to the constraints of morphological species identification. Environmental DNA metabarcoding offers a potent solution to these challenges. In this study, the community diversity of meiofauna and marine nematodes were investigated using eDNA metabarcoding and traditional morphological methods in the mangrove from Quanzhou Bay, Fujian Province, China. The findings showed that eDNA metabarcoding using the COI gene marker detected 19 meiofaunal groups, while morphological method identified only 4 groups, with copepoda and marine nematodes being recognized by both methods. Regarding abundance, copepoda (relative abundance: 81.01%) was the most dominant group identified by eDNA metabarcoding, whereas marine nematodes (abundance: 92.03%) was the most dominant group identified by the morphological method. The marine nematodes from five families and six genera were detected by eDNA metabarcoding, but those in morphological method were from 15 families and 23 genera. Daptonema and Terschellingia were common in both methods. In terms of abundance via eDNA metabarcoding, Daptonema had the highest relative abundance (85.71%), followed by Neochromadora (7.59%). In morphological method, Daptonema was also prominent (abundance of 15.95%), followed by Admirandus (12.36%). In conclusion, eDNA metabarcoding offers distinct advantages in identifying meiofaunal groups but exhibits notable discrepancies in abundance estimates compared to morphological method. It shows promise in monitoring marine nematodes diversity, with both methods highlighting Daptonema as the most abundant genus. The appropriate specific primers, a comprehensive database, and the definitive correlation between individual counts and sequences are crucial for the further widespread implementation of eDNA metabarcoding in monitoring meiofauna and marine nematodes diversity.